The Impact of the Minimum Wage on Unskilled Labour - Keyser, Wolfgang (The IIE, 2017)
Poverty is a growing problem (Kneebone, 2014; Quintal, 2017). American CEO and executive pay has risen at a faster rate than non-executive pay, consequently this has cast a spot light onto the issue of minimum wage as well as the plight of the poor (Semuels, 2017). In the American context, this has caused much lobbying and pressure to increase the minimum wage. Consequently, some states have instituted higher minimum wages, some up to $15 per hour. This has led to many businesses firing staff or reducing their hours (Boehm, 2017). This increase has especially hurt small/low margin businesses and the proposed changes leave little room for negotiation (McSwain, 2016). According to McSwain, (2016), some businesses will automate, while other will also cut benefits such as accrued income instead of leave, vacation days, et cetera. Research has shown that minimum wage hikes are ineffective and damaging (Sabia, 2014). In the South African Context, minimum wage hikes propose a major challenge as well. According to Businesstech.co.za, (2016), a minimum wage increase would result in disemployment of many unskilled workers. In response to politicians decrying economic equality (SA Gov, 2017), policy makers have proposed minimum wage hikes. However, research suggests that this is an ineffective and damaging tool to use to correct poverty (Sabia, 2014).
Keywords: Minimum wage; Unskilled workers; Unemployment